NDT Inspection and Stress Analysis of a Sherical Storage Tank. - Dr. Galanis N; Pefanis Themistoklis (2017)
Introduction, Liquefied Petroleum Gas (LPG), LPG in Sherical Storage Tanks, Construction of Spherical Tanks and Materials, Nondestructive Testing, NDT Methods, Visual Testing (VT), Magnetic Particle Testing (MT), MT Techniques, Advanced NDT Methods, Phased Array (PA), Time of Flight Diffraction (TOFD), Acoustic Emission (AE), Simulation, NDT Inspection Results, Conventiobnal NDT Methods, Visual Testing, Magnetic Particle Testing, Ultrasonic Testing, Advanced NDT Methods, Repairs, Welding Procedure Specification, Inspection after Repairing, Poat Weld Heat Treatment, Final NDT Inspection, Stress Analysis, 2D Modeling, Theoritical Approach - Hand Calcualation, Simulation, Theoritical Approach - Hand Calculation, Results, Conclusion, References, Bibliography, Appendix.